Pengaruh Environmental Concern dan New Environmental Paradigm Terhadap Pro-Environmental Behavior Peserta Didik Sma Negeri di Jakarta - Gebby Chrislia Puspaningrum; I Made Putrawan; Refirman Djamahar (Universitas Negeri Jakarta, 2023)
The increase in ecological crises occurs due to the lack of human awareness in protecting the environment. Efforts to overcome this by increasing pro-environmental behavior among students as the next generation. This study aimed to determine the effect of environmental concern and the new environmental paradigm toward students' pro-environmental behavior. The research was conducted at SMAN 54 Jakarta in the odd semester of the 2022/2023 school year with a sample of 100 students. The method used is a survey method through causal studies and analyzed by path analysis. The results of this research indicate that environmental concern has a direct effect on the new environmental paradigm significantly, the new environmental paradigm has a direct effect on pro-environmental behavior significantly, environmental concern has a direct effect on pro-environmental behavior significantly and environmental concern has an indirect effect on pro-environmental behavior through the new environmental paradigm significantly. Keyword: path analysis, environmental concern, new environmental paradigm, pro-environmental behavior, students